Consumer-to-consumer interpersonal relationships in electronic community : a 'digital' exploration of conceptions, attributes, consequences and personal values in a major UK sporting organisation - Hair , N (Cranfield University, 2004)
This doctoral thesis examines the conceptions of interpersonal relationships in a major UK sporting organization's electronic community (MUSO). Focusing on one text-based bulletin board, the research explores the meanings a sample of25 heavy users (insiders) attribute to their interactions with fellow members. Adopting an interpretivist / social constructionist perspective and a virtual ethnographic research strategy this research draws from George Kelly's Personal Construct Theory and Means-End-Chain analysis to explore these meanings as expressed in attributes of interactions, consequences and personal values. The research is split into two main sections, community and sample selection, and the main study. Working with one of the UK's leading moderating organizations, construct elicitation techniques revealed the means by which a sample of electronic communities could be differentiated on the basis of relational activity. Hinde's (1979) model of describing relationships together with a number of practical and ethical considerations were used as a means of identifying a suitable electronic community for the main study. Using a three stage electronic Delphi process, Moderators with experience in managing MUSO were canvassed for their opinions on heavy users (insiders). The main study comprises two approaches. The first involves a wider community interview drawing responses from over 500 members and identifying seven key themes of electronic community use. These are; conflict within the community, debates, entertainment, friendship, interaction, sharing and support. The second involves a number of in-depth electronic interviews exploring the conceptions of meanings of interpersonal relationships amongst insiders. Using a web based construct elicitation software package (WebGridIII) over 400 constructs from 25 participants on relational activity are identified. These are then explored using laddering and pyramiding techniques over instant messenger and email, revealing central attributes, consequences and personal values associated with their use of electronic community. The study identifies over 600 ladders comprising 1800 data points which are used to create hierarchical value maps for electronic community use across the seven key themes previously identified. The thesis makes several contributions to knowledge. To theory, it demonstrates the application of the means-end chain model to interpersonal relationships in electronic environments. It identifies the core values underpinning electronic community use of heavy users and the dominant perceptual pathways connecting the attributes of community use with personal values across the seven key themes. A contribution is further made in the categorization and selection process of electronic communities on the basis of relational activity, practical and ethical considerations. To methodology, the thesis explores the process of conducting virtual ethnography and presents a first hand day by day reflexive account of its activities and experience. The thesis also demonstrates the richness and abundance of data that can be collected using electronic research methods alone. Further contributions are made in the field of ethics identifying the means of safeguarding the integrity of the research process and the safety of participants. Finally practical managerial contributions are made in identifying the role and importance of interpersonal relationships in electronic community in the perceptions of its heavy users.